Collaborative project model based on culturally responsive teaching approach to strengthening social awareness - Iin Purnamasari; Singgih Adhi Prasetyo; Rofian; Nur Cholifah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The present study’s objectives are (1) to describe the CRT-based collaborative project model of social studies and fine arts; (2) to analyse the implementation of CRT in collaborative learning; and (3) to measure the influence of projects on students' social awareness. The research method used a qualitative approach with a case study method. The research subject is students who take social studies and fine arts courses in the PGSD Study Program with a research location in Semarang. Data collection techniques were observation to observe the collaborative learning process, interviews to explore the experiences of students and lecturers in projects, and documentation to analyse students' artworks as learning outcomes. Questionnaires are used to measure changes in students' social consciousness. Data Analysis techniques use qualitative analysis, which includes data reduction, data presentation, and conclusions. Thematic analysis is used to analyse patterns and themes in the collected data. Success Indicators are determined by increasing students' understanding of social issues through artworks based on local culture in Semarang, active participation of students in CRT-based discussions, and the existence of students' critical reflection on social reality manifested in course outputs, namely works with social issues in Semarang which are reviewed through expert lectures in an art exhibition called social art exhibition.